2019
DOI: 10.3390/cryst9120651
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Nanoscale Incipient Plasticity in GaAs and InP Crystal

Abstract: In this article, we exhibit the influence of doping on nanoindentation-induced incipient plasticity in GaAs and InP crystals. Nanoindentation experiments carried out on a GaAs crystal show a reduction in contact pressure at the beginning of the plastic deformation caused by an increase in Si doping. Given that the substitutional Si defects cause a decrease in the pressure of the GaAs-I → GaAs-II phase transformation, we concluded that the elastic–plastic transition in GaAs is a phase-change-driven phenomenon. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…10. The indentation hardness is representative of the plastic property of the material and coincides with the value of flow stress obtained in this work from the MD simulation, which possibly suggests that GaAs can flow plastically at a lower stress value than previously reported [38]. Moreover, the stress that is required to cause a phase transformation from GaAs-I to GaAs-II phase is of the order of 17.3 GPa, which is unlikely to occur during nanoscratching [42][43][44].…”
Section: Flow Stress and Plasticity In Gaassupporting
confidence: 87%
See 1 more Smart Citation
“…10. The indentation hardness is representative of the plastic property of the material and coincides with the value of flow stress obtained in this work from the MD simulation, which possibly suggests that GaAs can flow plastically at a lower stress value than previously reported [38]. Moreover, the stress that is required to cause a phase transformation from GaAs-I to GaAs-II phase is of the order of 17.3 GPa, which is unlikely to occur during nanoscratching [42][43][44].…”
Section: Flow Stress and Plasticity In Gaassupporting
confidence: 87%
“…A previous experimental work on doped GaAs material indicated the possibility that the phase transition from a zincblende structure (GaAs-I) to a rocksalt structure (GaAs-II) is responsible for the incipient plasticity during its nanoindentation process [38]. Without offering any direct evidence of the phase transition and at pressures as high as < 12 GPa, the work suggested that the GaAs-I to GaAs-II transition causes the plasticity in the material.…”
Section: Flow Stress and Plasticity In Gaasmentioning
confidence: 94%
“…The indentation‐generated dislocation loops are of the order of ≈10 4 with a critical radius of 2.15 nm for the first pop‐in event to trigger the plastic deformation in InP. [ 274 ] In Chrobak et al's [ 172 ] experiment, the current rise in InP at the pop‐in is two orders smaller than in GaAs (see Figure 19c,d), indicating that the dislocation contribution on the electrical conductivity in InP is minimal. Further, such a slight rise in the electrical current may be due to the sudden increase in the contact area.…”
Section: Applications Of Nano‐ecrmentioning
confidence: 99%
“…The I-h-t curve for c) GaAs shows a current spike, and d) InP shows an abrupt current rise at the pop-in event. Reproduced under the terms of the CC BY 4.0 license [172]. Copyright 2019, D. Chrobak et al, MDPI Publishing.…”
mentioning
confidence: 99%
“…A review of the scientific literature shows that the optoelectronic properties of InP are basically known, while the cause of its elastic-plastic transition has not yet been fully determined. Looking at the available data, the dominant role of dislocation activity becomes clear in the plastic deformation of InP [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], without the participation of structural phase transformations [ 18 ]. However, the results of mentioned structural investigations were carried out after nanoindentation experiments, so it is premature to exclude the effect of phase transformation on the incipient plasticity of InP.…”
Section: Introductionmentioning
confidence: 99%